The influence of microstructure on the fatigue crack growth rate in marine steels in the Paris Region - Igwemezie, Victor C.; Mehmanparast, Ali; Brennan, Feargal (Wiley, 2020)
This paper presents a study on the effect of microstructure on the fatigue crack growth (FCG) rate in advanced S355 marine steels in the Paris Region of the da/dN versus ΔK log–log plot. The environments of study were air and seawater (SW), under constant amplitude sinewave fatigue loading. Fundamentally, three phenomena (crack tip diversion, crack front bifurcation and metal crumb formation) were observed to influence the rate of FCG. These phenomena appear to be a function of the material microstructure, environment and crack tip loading conditions. The three factors retarded the crack growth by reducing or redistributing the effective driving force at the main active crack tip. A crack path containing extensively the three phenomena was observed to offer strong resistance to FCG. In SW, the degree of the electrochemical dissolution of the microplastic zone appears to be an additional primary factor influencing FCG in the steels
Keywords: S355 steel; Paris Region; microstructure; crack tip blunting; corrosion fatigue